The Effects of Investigative Sanctioning Systems on Wrongdoing, Reporting, and Helping: A Multiparty Perspective - Chui, Celia; Grieder, Manuel (Organization Science, 2020)
Over the past two decades, organizations have established sanctioning systems as an important component of their ethical infrastructures to detect and punish wrongdoing. However, empirical knowledge about the overall effectiveness of such systems remains limited. Existing studies have mostly adopted a single-party perspective even though many wrongdoing situations involve dynamic multiparty interactions between actors, recipients, and observers of wrongdoing. Moreover, most existing research has emphasized an economic perspective—that sanctioning systems only affect behavior because of economic considerations while crowding out ethical ones. In this research, we develop a moral and normative perspective of sanctioning systems. Using a novel experimental game design, our study focuses on the investigative dimension of sanctioning systems to examine their psychological and behavioral effects in actor–recipient–observer wrongdoing interactions. Findings reveal that investigative sanctioning systems influence wrongdoing, reporting, and helping behaviors as well as alter ethical and normative considerations, such that as systems become stronger, wrongdoing behaviors are judged as more unethical and perceived as less typical than when weaker systems are in place. These moral judgments and norm perceptions mediate the effect of investigative sanctioning system strength on wrongdoing behavior. Our research extends previous empirical and theoretical work on sanctioning systems by applying a more holistic perspective and by demonstrating that highly effective systems can serve as important behavioral guides because they activate and alter moral and normative considerations about wrongdoing.